Sport sciences research and Olympic host countries - Franchini, E.; Kokubun, E. (Sport Sciences for Health, 2019)
Olympic Games are the most prestigious multi-sport competition in the World. Due to its social and political importance, many countries propose candidate cities to host this competition. One of the alleged reasons to host this competition is the legacy it can generate, which include intangible aspects. Among the intangible legacy, the development of sport sciences is normally cited, because it can contribute to sport personnel enhancement, which consequently might positively influence sports practice and sports performance [1, 2]. Additionally, some countries also invest considerable amounts of resources to figure out between the most successful ones in the medal table, and the contribution of sport sciences in achieving such success has been reported recently [2]. Rees et al. [2] described that specific initiatives were considered successful in Australia and Great Britain. Specifically, these authors [2] indicated that the Australian Institute of Sport has been associated with the increased number of medals won by Australia from only 5 in 1976 Montreal Olympics to 60 medals in the 2000 Sydney Olympic Games. Great Britain`s investment in preparation for the Olympic Games increased from £235M in 2008 Beijing Olympics to £261M for 2012 London Olympics, to £355M for 2016 Rio Olympics [2]. A fourth place in Beijing, a third place in London and a second place in Rio Olympics followed these investments. Despite these successful actions, the optimization of procedures grounded on evidence-based approaches has been indicated as the best one for such large investments [2]. Thus, relying on sport sciences scientific production may be a relevant approach.